Understanding urban mental health impacts and how to create saner, happier cities. - Litman, Todd Alexander (My University, 2016)
This report examines how urban living affects residents' mental health and happiness, and ways to use this information to create saner and happier cities. Some often-cited studies suggest that urban living increases mental illness and unhappiness, but a critical review indicates that much of this research is incomplete and biased, and the issues are complex, involving trade-offs between risk factors. City living may increase some forms of psychosis and mood disorders, drug addiction, and some people's unhappiness, but tends reduce dementia, alcohol abuse and suicide rates, and many people are happier in cities than they would be living in smaller communities. This report examines specific mechanisms by which urban living can affect mental health and happiness, and identities practical strategies that communities and individuals can use to increase urban mental health and happiness. This analysis suggests that it is possible to create sane and happy cities.
Keywords: Stadtforschung; Großstadt; Gesundheit; Lebensbedingungen; Lärm; Verkehr; Kriminalität; Seelische Gesundheit; Urbanismus; Urbanität; Risikofaktor; Gesundheitsgefährdung